Pengaruh Kepemimpinan dan Beban Kerja Terhadap Kinerja yang di Mediasi oleh Kompensasi - Nurhayati Nurhayati; Syaiful Bahri; Bahril Datuk (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine the effect of leadership and workload on performance mediated by compensation for teachers at SD Muhammadiyah 18 Medan. The research method used is quantitative research, where the variables are measured using a Likert scale. The number of samples in this study were 34 teachers of SD Muhammadiyah 18 Medan. Data collection techniques used in this research are document studies and questionnaires. The data analysis technique used Structural Equation Modeling (SEM) using Smart-PLS. The results of the study indicate that: (1) Leadership has no significant effect on teacher performance at SD Muhammadiyah 18 Medan. (2) Directly leadership has no significant effect on compensation at SD Muhammadiyah 18 Medan. (3) Directly workload does not significantly affect teacher performance at SD Muhammadiyah 18 Medan. (4) Directly workload has a significant effect on compensation at SD Muhammadiyah 18 Medan. (5) Directly compensation has a significant effect on performance at SD Muhammadiyah 18 Medan. (6) indirectly leadership has no significant effect on performance through compensation. (7) indirectly the workload has no significant effect on performance through compensation.